2013
DOI: 10.1021/jp4105745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEGylation on Drug Entry into Lipid Bilayer

Abstract: Poly(ethylene glycol) (PEG) is a polymer commonly used for functionalization of drug molecules to increase their bloodstream lifetime, hence efficacy. However, the interactions between the PEGylated drugs and biomembranes are not clearly understood. In this study, we employed atomic-scale molecular dynamics (MD) simulations to consider the behavior of two drug molecules functionalized with PEG (tetraphenylporphyrin used in cancer phototherapy and biochanin A belonging to the isoflavone family) in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Short chain PEG groups, such as [–O(CH 2 CH 2 O) 3 ⋅ CH 3 ] when bonded to sensitizers can reduce self‐aggregation , and retain some propensity to localize in cell membranes compared to unsubstituted sensitizers . Therefore, we surmised that a galloyl unit carrying three PEG groups could be bonded to pheophorbide silica end‐tips of a pointsource PDT device.…”
Section: Resultsmentioning
confidence: 99%
“…Short chain PEG groups, such as [–O(CH 2 CH 2 O) 3 ⋅ CH 3 ] when bonded to sensitizers can reduce self‐aggregation , and retain some propensity to localize in cell membranes compared to unsubstituted sensitizers . Therefore, we surmised that a galloyl unit carrying three PEG groups could be bonded to pheophorbide silica end‐tips of a pointsource PDT device.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we have also shown that the spatial distribution of p-THPP (a tetraarylporphyrin) in a POPC bilayer is more complex. 49 It is characterized by two preferred positions: one at 1.51 nm from the bilayer center, corresponding to a location of the lipid carbonyl groups, and another at 0.81 nm from the bilayer center. To gain more detailed insight into the preferred The Journal of Physical Chemistry B Article arrangement of p-THPP in lipid membranes, here we performed simulations in two different bilayers, namely POPC and DLPC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been adopted in theoretical studies of biological membrane models (Tieleman et al 1997;Mark 2010, 2012) and partitioning and interaction of drugs in lipid bilayers (Fuchs et al 1990;Omote and Al-Shawi 2006;MacCallum and Tieleman 2006;Bemporad et al 2004). Indeed, MD simulations have contributed significantly to the understanding of the structure, dynamics and effects of biological molecules in lipid bilayers (Seydel and Wiese 2002;Xiang and Anderson 2006;Yamamoto et al 2012;Rissanen et al 2014;Almeida et al 2017). However, due to the variety of classical force fields available, it is important to compare the results obtained from the simulations with the experimental data to validate the simulation force field and protocols.…”
Section: Introductionmentioning
confidence: 99%